Two fragments of Punic wheel-made clay figurines from the Tophet of Bithia – Su Cardolinu (Domus de Maria – South Sardinia) - Stefano Floris (Gerión)
The paper presents and discusses two recently discovered fragments of wheel-made clay figurines recovered during the renewed investigations conducted by the Ca’ Foscari University of Venice in the Tophet of Bithia, situated on the islet of Su Cardolinu. These two specimens, representing the first instances of wheel-made clay figurines found in Bithia outside of the well-known batch of “suffering devotees”, hold significant implications for our understanding of the history of the Tophet of Su Cardolinu and, more generally, the settlement of Bithia.